Construction and Validation of an Instrument to Evaluate the Characteristics of University Social Responsibility in University Students - Valentina Bolio Domínguez; Leny Michele Pinzón Lizarraga (Universidad Autónoma de Madrid, 2019)
The present article show results obtained from the construction and statistical validation of an instrument designed for the analysis of University Social Responsibility (rsu) characteristics in university students. Despite of the different theoretical proposals available about rsu, the development of measuring instrument related to social responsibility and their influence among students for social change is on its early stages of development. The construction of the instrument including different rsu characteristics was done in five stages: three were related to designing and construction and two were related to the application, validation, and development of the final version. Literature review allowed the creation of a scale of 47 items divided into seven characteristics of a socially responsible student: consciousness, commitment, controversy with civility, respect to diversity, citizenship, social justice and change. The previous items can be grouped in four dimensions corresponding to Retolaza's Model of Social Change: personal transformation, transformation of relationships, transformation of cultural patterns, and structural transformation. The instrument was analyzed by eight experts in order to assess its content and validity followed by its evaluation in a pilot test with a sample including 102 students from two private universities. The statistical analysis showed high internal consistency in all seven characteristics and in each four dimensions. The factorial analysis showed consistency in all four dimensions found in the Retolaza model. The content validity of the instrument was analyzed by eight expert judges and subsequently the instrument was applied to a pilot sample of 102 students from two private universities. The statistical analysis showed a high general internal consistency and also high internal consistency in each of the dimensions. The factor analysis showed consistency in all four dimensions found in the Retolaza Model.